Ocean cavity regime shift reversed West Antarctic grounding line retreat in the late Holocene - Lowry, Daniel P.; Han, Holly K.; Golledge, Nicholas R.; Gomez, Natalya; Johnson, Katelyn M.; McKay, Robert M. (Nature communications, 2024)
Recent geologic and modeled evidence suggests that the grounding line of the Siple Coast of the West Antarctic Ice Sheet (WAIS) retreated hundreds of kilometers beyond its present position in the middle to late Holocene and readvanced within the past 1.7 ka. This grounding line reversal has been attributed to both changing rates of isostatic rebound and regional climate change. Here, we test these two hypotheses using a proxy-informed ensemble of ice sheet model simulations with varying ocean thermal forcing, global glacioisostatic adjustment (GIA) model simulations, and coupled ice sheet-GIA simulations that consider the interactions between these processes. Our results indicate that a warm to cold ocean cavity regime shift is the most likely cause of this grounding line reversal, but that GIA influences the rate of ice sheet response to oceanic changes. This implies that the grounding line here is sensitive to future changes in sub-ice shelf ocean circulation. Using ice sheet model and glacio-isostatic adjustment model simulations and paleoclimate proxies, this work demonstrates that the most likely cause of past West Antarctic grounding-line reversal was a regime shift from a warm to cold ocean cavity.